Current demand of high performance inverters for renewable energy systems - Daher, Sérgio (2007)
This paper points out that versatile stand-alone renewable energy systems demand on at least one robust battery inverter. Despite of the employed system configuration, it is shown that the battery inverter should be capable to practically support all load demand. In practice, improved characteristics of reliability, surge power capability and efficiency are essential to guarantee long term and flexible operation for such systems. In addition, it is shown that these inverters can be optimized by considering the typical load profile commonly found in stand-alone applications. It is shown that multilevel topologies can be very suitable for these applications due to their inherent high efficiency and robustness. A prototype of 3 kVA was implemented and it has proved itself to be robust. Peak efficiency of 96.0% was achieved: value that is higher than similar high performance inverters currently available in the market.